(untitled) (Research, Society and Development, 2020)
The objective of this study was to carry out a narrative bibliographic review on the importance of dental care for people with special needs (PSN), emphasizing attention to the use of medication, restraints, parental care and multidisciplinarity among professionals and family members. Scientific articles in Portuguese, English or Spanish, published from 2000 to 2020, were selected from the databases: PubMED, BBO, LILACS, SCIELO. The research on the platforms took place through the following descriptors: special patients, dental care and oral health. From the data obtained, it was observed that PSN generally manifest more severe oral conditions. These individuals usually have motor limitations resulting from this condition, difficulties in cooperation and aggressive behaviors, which impairs oral hygiene, even though, in most cases, they have a caregiver responsible for it. Thus, dentistry for PSN is a specialty that requires greater selectivity in the techniques that will be used to perform the procedures, in addition to greater attention to the patient’s systemic conditions. In addition, there is a need for the dental surgeon to provide the necessary information, demonstrate oral care, indicate auxiliary techniques and, at the same time, encourage caregivers to continue the oral hygiene of these patients.